Analysis of Students’ Mathematical Critical Thinking in Solving Function Derivative Problems based on Gender Differences - Astuti, Sri Ayu Budi; Siregar, Rama Nida; Rangkuti, Rizki Kuniawan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Critical thinking is a vital skill in solving mathematical problems, particularly in calculus where understanding derivative functions is essential. Previous research indicates that gender differences may influence students’ cognitive strategies and performance in mathematical problem-solving. This study aims to analyze the critical thinking abilities of mathematics education students in solving derivative function problems, with a specific focus on gender differences. A qualitative descriptive method with a case study approach was employed. The participants were male and female students selected through purposive sampling from a mathematics education program. Data collection techniques included critical thinking tests, semi-structured interviews, and documentation. The analysis framework was based on Facione’s critical thinking indicators: interpretation, analysis, evaluation, inference, and explanation. Thematic analysis was used to examine qualitative data, while descriptive statistics summarized students' performance on the tests. Results revealed that female students generally achieved higher critical thinking scores than their male counterparts. They showed a stronger tendency to employ analytical and reflective strategies, whereas male students typically adopted more procedural and direct approaches. Both groups encountered significant difficulties in the evaluation and explanation phases, which are crucial to advanced critical thinking. The study concludes that gender plays a role in shaping students’ critical thinking strategies in solving derivative problems. These findings underscore the importance of gender-responsive and adaptive instructional strategies in calculus learning to enhance students' logical reasoning and overall critical thinking development in higher education mathematics instruction.